1997
DOI: 10.1007/bf02467228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quenching regimes on the structure and properties of an alloy from the Al−Mg system

Abstract: All industrial alloys of the AI-Mg system correspond to the region of the a-solid solution of the phase diagram. Domestic alloys AL8 and AL27-1 and foreign alloys 520 (USA) and LM-10 (Great Britain) with a high magnesium content (9 -11%) have high mechanical properties after quenching. However, they possess a high sensitivity to natural aging under conditions of long-term operation or storing, which causes their embrittlement. The aim of the present work consists in developing an AI-Mg-base composition quenche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…After natural aging the strength parameters increase insubstantially, but the elongation decreases considerably. In combination with the relatively low yield limit (%.2 ~ 0.5 %) this can cause embrittlement of the alloy and failure of the castings.In order to eliminate the negative effect of natural aging, we have developed a heat-treatment regime for an experimental alloy, which includes quenching in boiling water after a hold at 435~ for 20 h and aging at 80-100~ for 35-45 h [1].The aim of the present work consists in refining the regime in order to guarantee the specified level of properties and their stability in the process of subsequent operation and to save energy.A preliminary study has shown that the temperaturetime regime of quenching mentioned above is optimum because it provides a full dissolution of magnesium and eliminates burning of the alloy, which is an irreparable defect in heat treatment.We used the method of mathematical design and tested a two-stage aging regime with variation of the variable within the following ranges: …”
mentioning
confidence: 99%
“…After natural aging the strength parameters increase insubstantially, but the elongation decreases considerably. In combination with the relatively low yield limit (%.2 ~ 0.5 %) this can cause embrittlement of the alloy and failure of the castings.In order to eliminate the negative effect of natural aging, we have developed a heat-treatment regime for an experimental alloy, which includes quenching in boiling water after a hold at 435~ for 20 h and aging at 80-100~ for 35-45 h [1].The aim of the present work consists in refining the regime in order to guarantee the specified level of properties and their stability in the process of subsequent operation and to save energy.A preliminary study has shown that the temperaturetime regime of quenching mentioned above is optimum because it provides a full dissolution of magnesium and eliminates burning of the alloy, which is an irreparable defect in heat treatment.We used the method of mathematical design and tested a two-stage aging regime with variation of the variable within the following ranges: …”
mentioning
confidence: 99%